Analysis of landscape performance assessment by key stakeholders in a transfrontier conservation area. (4th July 2018) - Chitakira, Munyaradzi; Torquebiau, Emmanuel; Ferguson, Willem; Mearns, Kevin
Abstract: Stakeholder engagement has become an important aspect of sustainable natural resources management. This study analysed a landscape performance assessment by local and 'external' stakeholders in a transfrontier conservation area in Southern Africa. The landscape was divided into three agro-ecological zones and focus group discussions were facilitated for stakeholders to evaluate the landscape based on four ecoagriculture dimensions (production, conservation, livelihoods and institutions). The conservation dimension showed the best performance and the overall score for the landscape was 2.97, implying a fairly good performance. Perceptions and ratings did not significantly differ by age, gender or stakeholder groups. We conclude that despite their low levels of formal education and training, communal farmers can assess the performance of local landscapes in a consistent way. This study provides information about the degree to which the landscape under focus conformed to the main ecoagriculture goals and can guide development planning and extension service provision.